Improvement of frying technology for small-scale barbecue peanut production - Fermin, Brenda Cayabyab; De Leon, Sonia Y. (1993)
The main objective of this study is to improve the frying technology for small-scale barbecue peanut production. The first phase of the study consisted of lab-scale frying, which primarily aimed to determine the extent of reusability of a selected brand of oil in the frying of peanuts, with free fatty acid (FFA) test and smoke point as bases. Results showed that a peanut-to-oil ratio of 0.42 g peanuts/ml of oil, the oil was acceptable up to the 195th usage. At this point, the oil reached the maximum tolerable limit for FFA in nuts -- 0.3%; and its smoke point decreased from 425°F to 360°F. Sensory evaluation of the barbecue peanuts fried in different stages of the frying life of the oil showed that, although these were inferior to the samples fried in fresh oil, these were still generally acceptable, and did not reach the "dislike" range. In the second phase, a frying equipment was especially designed and fabricated for small-scale barbecue peanut production. It had a maximum capacity of 4.0 kg peanuts in 9.5 l of oil. It was made of stainless steel and had vertical sides, in order to avoid interaction with the food and to retard oil deterioration, respectively. Specifications were set for one small-scale production run, which was found to give 110% yield.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peanuts